Use of chondroitin sulphate and glucosamine sulphate in degenerative changes in TMJ: a systematic review - Machado,Eduardo (2012)
INTRODUCTION: Degenerative changes in Temporomandibular Joint (TMJ) have increased in prevalence and severity over the years. Within this context, it's necessary to obtain safe and effective therapies for control and management of the patient in cases of osteoarthritis and osteoarthrosis of the TMJ. Therapeutic options range from intra-articular infiltration protocols, occlusal splints, pharmacological therapies and physiotherapy and educational measures. The alternative treatment with structure-modifying agents, like as chondroitin and glucosamine sulphates, showed promising results, and especially safety. Thus, through a systematic literature review, this study aimed to analyze and discuss effectiveness and safety of chondroitin and glucosamine in degenerative changes of the TMJ. METHODS: Survey in research bases MEDLINE, Cochrane, EMBASE, Pubmed, Lilacs and BBO, between the years of 1966 and January 2009, with focus in randomized clinical trial (RCTs) and quasi-randomized clinical trials, systematic reviews and meta-analysis. RESULTS: After application of the inclusion criteria 2 articles were selected, both randomized controlled double-blind clinical trials, which evaluated the effectiveness of chondroitin and glucosamine in degenerative changes of the TMJ. CONCLUSIONS: There is the necessity of further RCT, with representative samples and long follow-up time, to obtainment more precise cause-effect relationships and to achieve an effective and objective protocol involving chondroitin and glucosamine in cases of degenerative changes of the TMJ.